iPad 2 - Biersdorfer, J. D. (Missing manual., 2011)
Looks at the features and functions of the iPad2, covering such topics as accessing the Internet, setting up an email account, using built-in apps, playing games, using iTunes, watching videos, and syncing with MobileMe.--